Anomalous size effect in micron-scale CoCrNi medium-entropy alloy wire. (1st July 2021) - Chen, Jin-Xi; Chen, Yan; Liu, Jun-Peng; Liu, Tian-Wei; Dai, Lan-Hong
Abstract: Micron-sized CoCrNi medium-entropy alloy (MEA) wires are successfully fabricated by Taylor-Ulitovsky method for the first time. The wires of two different sizes, with diameters of 40 and 100 microns, exhibit an excellent combination of tensile strength and ductility. In-depth microstructure characterization indicates the superior mechanical properties stem from the synergy of Lomer-Cottrell locks, mechanical nano-twinning and HCP stacking. Surprisingly, an anomalous size effect is presented in the tension of these microwires, i.e., the much higher tension strength and ductility are observed in the 40 micron-wire, in sharp contrast to conventional single-principal element alloys only showing negligibly minor tension size effect. Much higher density of geometrically necessary dislocation accompanying heterogeneous deformation is observed in 40 micron-wire, leading to a high strain gradient, which is in turn joined with multiple deformation twins giving rise to high strength and ductility in 40 micron-wire. Graphical abstract: Image, graphical abstract